THE EFFECT OF MILD EXERCISE ON ATTENTION PERFORMANCE AND STRESS LEVEL - MOHD ZULFAKHAR, ANIS INSYIRAH (Universiti Teknologi PETRONAS, 2016)
The project propose is to study the effect of mild exercise on attention performance and stress level by develop an experimental protocol and a program or recipe to pre-process fNIRS data in MATLAB. In addition, to perform a statistical analysis to study the effects. In this study, we proposed repeated moderate cycling exercises to improve performance attention and reduce stress levels as continuous work under stress will disrupt attention and reduce the performance level of a person. The equipment that used to measure the brain signal in this project are Optical Topography and EEG because every neuroimaging has their weakness. EEG is poor in spatial resolution and sensitive to noise and motion artefacts, while fNIRS is less affected by motion artefacts and offers better spatial resolution of cortical activation. By using this two non-invasive Neuroimaging modalities, we can improve the spatial and also temporal resolution.